Development of digital pop-up book Pancasila education to improve learning outcomes - Ayuningtyas, Falensia Indah; Widodo, Susilo Tri (Jurnal Prima Edukasia, 2026)
The limited use of innovative and digital based learning media reduces students' opportunities to gain meaningful and relevant learning experiences in real-life contexts. This situation has implications for low learning outcomes in Pancasila Education and becomes an obstacle in strengthening 21st-century skills. This research aims to develop learning media while assessing the feasibility and effectiveness of Digital Pop-Up Book media in Pancasila Education subjects. The research approach applied is RnD with reference to the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects involved teachers and fifth-grade students of Pener 01 Elementary School, Pemalang, Indonesia. Data collection techniques included expert assessments, student and teacher response questionnaires, and pre- and post-tests compiled based on learning outcome indicators. Data were analyzed using normality tests, homogeneity tests, t-tests, and N-Gain tests. The results of the t-test analysis obtained a Sig. (2-tailed) value of 0.000 (<0.05), which indicates a significant difference between the pre-test and post-test scores. In addition, the N-Gain value of 0.70 (70.0%) falls within the high category, indicating a significant increase in student learning outcomes. The developed Digital Pop-Up Book media was deemed highly feasible, as indicated by validation scores of 89% from media experts and 80% from material experts. User responses also showed very positive results, with a student response percentage of 95% and a teacher response of 90%. Thus, the Digital Pop-Up Book media has proven feasible and effective for implementation in Pancasila Education. The findings suggest that the integration of Digital Pop-Up Books serves as a strategic solution for educators to transform abstract civic values into engaging visual experiences, ultimately fostering more dynamic and meaningful 21st-century learning in elementary schools.